Skills Acquisition: Imperative For Business Studies Educators Among Secondary Schools In Rivers State - Nwanaka , C. R.; Amaehule , Samuel (Mediterranean Journal of Social Sciences, 2011)
Fundamentally, the placement of Skill Acquisition for self-reliant education which leads to sound productivity in thesociety cannot overemphasized. On that note, skills are appropriate towards the contribution and development of both individualand the nation at large. These include attitude of government, acquisition process, infrastructure and equipment and studentinterest. We found out that these problems obstruct the sound process of acquisition and recommend that government andprivate sectors should take it as a matter of urgency to eradicate these problems to have a clear skill acquisition through soundcurriculum of Business Studies.